Nudging self-employed women to contribute to social security - Lorena Heller; Rodrigo López; Ricardo Nogales (Inter-American Development Bank (IDB), 2024)
Over 30 percent of female workers are self-employed across Latin America, relying on this mode of work for subsistence. Self-employment in the region is regularly marked by the absence of health insurance and lack of pension benefits. Despite the aspirations of many women to gain access to these benefits, they are persistently overrepresented among the socially unprotected part of the workforce. To address this issue and explore potential solutions, we conducted a laboratory experiment in Bolivia to assess the efficacy of nudges to influence the behavior of self-employed women. Participants were randomly assigned to one of six groups, each receiving either an informative message highlighting the benefits of contributing to a long-term pension system, a message emphasizing the advantages of health insurance, or a nudge aimed at reducing the effort and costs associated with enrolling in a savings or retirement plan. Our findings indicate that informative messages alone were effective in increasing voluntary contributions to experimental pension and health insurance schemes. Reductions in time and effort required for enrollment did not lead to a significant increase of voluntary contributions. Moreover, we found that the effectiveness of these interventions varied depending on the type of worker, with high-effort workers being the most responsive.
Keywords: C91; J16; J20; J70; 330; Self-employment; Pension system; Health insurance; Laboratory experiment